RANCANG BANGUN APLIKASI SURAT KETERANGAN HASIL PENGUJIAN ELEKTRONIK BERBASIS QR CODE PADA UPTD METROLOGI LEGAL KOTA PADANG - Harishandi, Harishandi; Irfan, Dedy (INCARE, International Journal of Educational Resources, 2021)
Making a Test Result Certificate (SKHP), managing SKHP data, Errors in making offline data recaps are very ineffective and time consuming. For that we need a web application that can manage the Test Result Certificate (SKHP) efficiently. The purpose of this research is to build a QR code-based electronic test result letter application at the UPTD Metrology Legal Padang City. The design in this web application uses the waterfall model method, which is a very structural method, where the steps of this method are: the process of planning, analysis, design, and implementation of the system. The architecture in the design of the application for a certificate of electronic test results based on QR code at the Padang City Legal Metrology UPTD uses the MVC architecture (model, view, controller).The main features of this application are: user management, master data management, SKHP data management, online certificate management, and management of criticism and suggestions. The system is built using the PHP framework, which is a framework built using the PHP programming language. By conducting an independent trial of the developed system, it was found that the application of the certificate of test results information can facilitate the making of SKHP, SKHP data management, online certificate management, and management of criticism suggestions.